Smart contracts in OTC derivatives trading: Legal aspects - Kirill A. Bobkov (Цифровое право, 2020)
The articles focuses on opportunities and problems connected with implementation of smart contracts into “over-the-counter” derivatives trading. The importance of success of professionals who work on this cannot be underestimated: the volume of “over-the-counter” derivatives market is huge, its automatization and transparency provided by implemented smart contracts could dramatically increase its economic efficiency. In this study, the author aims at answering the following question: what aspects of “over-the-counter” derivatives trading could take a quantum leap because of the implementation of smart contacts and, per contra, what aspects could not benefit from implementation of underlying technologies at all. The author starts with the overview of “over-the-counter” derivatives market, investigates the matter of its internal design, main features and the structure of legal documentation used by market participants. Then the article provides the analysis of smart contract phenomenon, summary of its engineering aspects and difficulties connected with the implementation of smart contracts as a practical matter, including underlying legal issues. The third part is a synthesis of ideas indicated in previous parts. Herein the author examines the perspectives of adoption of smart contracts in “over-the-counter” derivatives trading, identifies the problems that cannot be resolved yet: different parts of legal relations existing between market participants shall be structured in a flexible way and shall be subject to revision under specific conditions. Smart contracts in their turn cannot be considered as a flexible tool and the revision of their terms requires the input from highly experienced specialists that dramatically increases the costs of their implementation and maintenance. As a matter of conclusion, the author gives recommendation to potential developers of smart contacts to implement them only in relation to the automatization of payments and deliveries as at the moment the clearing can be considered as the most appropriate area for the implementation and use of smart contracts.